1986
DOI: 10.1016/s0735-1097(86)80329-1
|View full text |Cite
|
Sign up to set email alerts
|

Early thrombolysis in acute myocardial infarction: Limitation of infarct size and improved survival

Abstract: The effect of thrombolysis in acute myocardial infarction on infarct size, left ventricular function, clinical course and patient survival was studied in a randomized trial comparing thrombolysis (269 patients) with conventional treatment (264 control patients). All 533 patients were admitted to the coronary care unit within 4 hours after the onset of symptoms related to the infarction. Baseline characteristics were similar in both groups. Informed consent was requested only of patients allocated to thrombolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(92 citation statements)
references
References 42 publications
3
88
0
1
Order By: Relevance
“…More of the left ventricular wall was infarcted in patients who died of congestive heart failure than in those who died of cardiac rupture. These findings are similar to those reported in patients without coronary thrombolysis who died of AMI 16,20,21 The present data revealed that (1) there was no significant difference in the infarct size/risk area ratio between groups I and II, (2) CBN was diffusely present in group I but almost absent in group II, (3) the infarct size/risk area ratio and the percentage of the infarct containing CBN varied considerably in group III.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More of the left ventricular wall was infarcted in patients who died of congestive heart failure than in those who died of cardiac rupture. These findings are similar to those reported in patients without coronary thrombolysis who died of AMI 16,20,21 The present data revealed that (1) there was no significant difference in the infarct size/risk area ratio between groups I and II, (2) CBN was diffusely present in group I but almost absent in group II, (3) the infarct size/risk area ratio and the percentage of the infarct containing CBN varied considerably in group III.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the results may be most applicable to this subgroup of patients. CBN is considered to be caused by (1) reperfusion after ischemia or anoxia, "0"2 (2) Therefore it is necessary to develop methods to protect against CBN to reduce infarct size in human AMI.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the infarct depends mostly on the distribution of the occluded artery, though the collaterals may limit it to the subendocardial layer (2). Early thrombolytic treatment limits the size of the infarct (3,4). Therefore early identification and confirmation of AMI are essential for rapid and correct decision making and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of thrombolysis is enhanced by early treat ment and the re-establishment of coronary patency (8). This requirement makes widespread intracoronary (i.c.)…”
mentioning
confidence: 99%